The effectiveness of skimming and scanning strategies in improving reading comprehension among EFL learners - Husnul; Putra, Bayu Karunia; Azmi, M. Ulul; Wati, Kurnia; Ernawati, Novi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: As a developing country with a vast and diverse archipelago, Indonesia requires a greater number of high-quality human resources capable of competing both nationally and internationally. One such strategy is the expanded development of English language education to strengthen human resources. Foreign a significant challenge in the learning process is the limited availability of both formal and informal platforms for students to practice the language, which hampers their progress. For EFL learners, reading is essential for acquiring the language, expanding vocabulary, and gaining broader knowledge and experiences. Methods: The research was carried out with 25 second-year students from class XI Science 1 at MA Darul Muhajirin Praya. The research utilized a Classroom Action Research (CAR) design, implemented over two cycles. Each cycle consisted of four phases: planning, implementation, observation, and reflection. Data were gathered through tests, observation sheets, and documentation. Findings: The findings indicated a significant improvement in students' reading comprehension, marked by an average score increase of 8.97% from the pre-test to the second post-test. During the pre-test, only 1 student (4%) met the minimum passing standard (KKM), with an average score of 54.6. In the first post-test, 9 students (29.45%) achieved the passing score, with the average rising to 70.88. By the second post-test, 19 students (76%) had passed, with the average score reaching 77.24. Conclusion: This study concludes that applying skimming and scanning techniques greatly enhances students' reading comprehension. Incorporating these strategies into classroom English instruction effectively improves students' understanding of narrative texts, as evidenced by the findings of the action research. Novelty/Originality of this article: This study highlights the effectiveness of integrating skimming and scanning techniques into classroom English instruction for EFL learners. The novelty lies in demonstrating, through classroom action research, how these strategies significantly improve students’ comprehension of narrative texts in a measurable and systematic way.